FUZZY KLUSTERING SHORT TIME SERIES UNTUK SEGMENTASI PELANGGAN (studi kasus: Sampel Load Pelanggan PLN di Yogyakarta) - , MARIA TITAH JATIPANINGRUM ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Clustering is a descriptive statistical technique that helps in determining the central points, is the most fundamental concepts to determine the pattern of the data in the segmentation data. The advantages of fuzzy clustering gives a fuzzy clustering partition data, stronger, broader, and more realistic than crisp partition. In this research, given an empirical analysis with fuzzy clustering method with short time series distance. The reason behind it, because of capturing time interval information from sample data. Analysis of empirical data is used time series data i.e. customers loads sample Yogyakartaâs State Electricity Enterprise..e